Geography and Sacred Symbolism of Muktinath Shrine, Nepal - Messerschmidt, Donald A. (Himalayan Review, 2011)
Not available. Key words: Sacred Symbolism; Muktinath Shrine; Hindu pilgrim; Shaligram; Nepal The Himalayan Review Vol. 15, 1983-18984 Page: 39-57 Uploaded Date: April 13, 2011